Understanding the Complexity of Hypertension with Sarcopenia by Scientometric Analysis - Zou J; Liu Y; Tian C; Wang L; Li S; Ran J; Yang X; Nie G; Peng W (Journal of Multidisciplinary Healthcare)
Jingfeng Zou,* Yiting Liu,* Chunhui Tian,* Liping Wang, Shaotian Li, Jiajia Ran, Xin Yang,* Guqiao Nie, Wen Peng Department of General Practice, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, WuHan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guqiao Nie; Wen Peng, Department of General Practice, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Jie Fang avenue, WuHan, Hubei, 1227, People’s Republic of China, Email 313848396@qq.com; pengwen666@sina.comObjective: The scientometric analysis was aim to focus on recent studies and clarify new research directions on hypertension with sarcopenia. We hope to provide comprehensive insights or actionable recommendations for clinicians or policymakers.Methods: The Web of Science Core Collection database (WoSCC) from 2004 to 2023 for analysis was used. And VOSviewer, CiteSpace, and Origin software were utilized for scientometric analyses.Results: The United States was the primary contributor to 1,994 studies on hypertension with sarcopenia. The University of São Paulo emerged as the most prolific institution, with Morrell Nicholas W. being the most influential scholar and Cruz-Jentoft A.J. being the most co-cited author. PLoS One was the most prolific journal, whereas Circulation was the most relevant journal. Research has focused not only on physiological, biochemical, and cell biological mechanisms but also on sarcopenia associated with other diseases and involved in various fields, highlighting the complexity of the area and the need for integrative treatment. Keyword analysis revealed that, in addition to hypertension and sarcopenia, other topics such as obesity, pulmonary hypertension, old age, metabolic syndrome, inflammation, hypoxia, exercise, insulin resistance, and revascularization attracted attention. In recent years, COVID-19, mitochondria, handgrip strength, etc. have been hot topics, but aging, skeletal muscle, weight loss, diabetes, obesity, metabolic syndrome, insulin resistance, heart failure, mitochondria, mortality, exercise, and physical activity seems to bridge hypertension and sarcopenia research.Conclusion: This study highlights the distribution of fields, the structure of knowledge and the evolution of major research topics related to hypertension in patients with sarcopenia. Identifying keyword hotspots enhanced the comprehension of occurrence, development, and future research trends related to the topic.Keywords: hypertension, sarcopenia, scientometric analysis, visualization